Consumptive and non‐consumptive effects of predators vary with the ontogeny of their prey. Issue 5 (8th April 2019) - Pessarrodona, Albert; Boada, Jordi; Pagès, Jordi F.; Arthur, Rohan; Alcoverro, Teresa
Abstract: Predators exert a strong influence on ecological communities by reducing the abundance of prey (consumptive effects) and shaping their foraging behavior (non‐consumptive effects). Although the prevalence of trophic cascades triggered by non‐consumptive effects is increasingly recognized in a wide range of ecosystems, how its relative strength changes as prey individuals grow in size along various life stages remains poorly resolved. We investigated how the effects of predators vary with the ontogeny of a key herbivorous sea urchin, which is responsible for transforming diverse macroalgal forests to a barren state dominated by bare rock and encrusting coralline algae. We conducted a series of field and laboratory experiments to determine how susceptibility to predation, prey behavioral responses, and grazing impact on algal cover vary with sea urchin size. The consumptive effects of predators were greater on smaller sea urchin size classes, which were more susceptible to predation. Unexpectedly however, predator non‐consumptive effects acted only on larger sea urchins, significantly reducing their grazing activity in the presence of predator cues. Crucially, only these larger sea urchins were capable of overgrazing macroalgae in the field, with non‐consumptive effects reducing sea urchin foraging activity and macroalgal grazing impact by 60%. The decoupling between risk and fear as prey grow indicates that the strength of consumptive and non‐consumptive trophic cascades may act differently at different ontogenetic stages of prey. While the consumptive effects of predators directly influence population numbers, the consequences of non‐consumptive effects may far outlive consumptive effects as prey grow, finding refuge in size, but not from fear.